Role of circulating T follicular helper subsets following Ty21a immunization and oral challenge with wild type S. Typhi in humans - Booth, Jayaum S.; Rapaka, Rekha R.; McArthur, Monica A.; Fresnay, Stephanie; Darton, Thomas C.; Blohmke, Christoph J.; Jones, Claire; Waddington, Claire S.; Levine, Myron M.; Pollard, Andrew J.; Sztein, Marcelo B. (Frontiers in Immunology, 2024)
Salmonella Typhi (S. Typhi) infection and disease remains incomplete. T follicular helper cells (TFH), an important link between cellular and humoral immunity, play an important role in the development and production of high affinity antibodies. While traditional TFH cells reside in germinal centers, circulating TFH (cTFH) (a memory subset of TFH) are present in blood. We used specimens from a typhoid controlled human infection model whereby participants were immunized with Ty21a live attenuated S. Typhi vaccine and then challenged with virulent S.Typhi. Some participants developed typhoid disease (TD) and some did not (NoTD), which allowed us to assess the association of cTFH subsets in the development and prevention of typhoid disease. Of note, the frequencies of cTFH were higher in NoTD than in TD participants, particularly 7 days after challenge. Furthermore, the frequencies of cTFH2 and cTFH17, but not cTFH1 subsets were higher in NoTD than TD participants. However, we observed that ex-vivo expression of activation and homing markers were higher in TD than in NoTD participants, particularly after challenge. Moreover, cTFH subsets produced higher levels of S. Typhi-specific responses (cytokines/chemokines) in both the immunization and challenge phases. Interestingly, unsupervised analysis revealed unique clusters with distinct signatures for each cTFH subset that may play a role in either the development or prevention of typhoid disease. Importantly, we observed associations between frequencies of defined cTFH subsets and anti-S. Typhi antibodies.Taken together, our results suggest that circulating TFH2 and TFH17 subsets might play an important role in the development or prevention of typhoid disease. The contribution of these clusters was found to be distinct in the immunization and/or challenge phases. These results have important implications for vaccines aimed at inducing long-lived protective T cell and antibody responses.